Cutaneous leishmaniasis: Review Article - Al-Ma'amouri, May Y. (Journal for Research in Applied Sciences and Biotechnology, 2023)
Leishmaniasis is a protozoal infection caused by a number of different species in the Leishmania genus. Sandflies are the vectors for the transmission of these protozoa to humans. When macrophages are triggered into a leishmanicidal state, a clinical recovery occurs. In particular, the T-helper cell type 1 (Th1) response is responsible for this, and it is also responsible for preventing the recurrence of latent chronic infection. Regardless of the disease's clinical manifestation, antimonial drugs are the treatment of choice. Amphotericin B is the second-best treatment option. This study focuses on the pathology and treatment of cutaneous leishmaniasis.